Greater Dietary Inflammatory Potential Is Associated With Higher Likelihood of Abdominal Aortic Calcification - Qin, Zheng; Chang, Kaixi; Liao, Ruoxi; Jiang, Luojia; Yang, Qinbo; Su, Baihai (Frontiers in Cardiovascular Medicine, 2021)
Aims: We aimed to assess the association between dietary inflammation index (DII) and abdominal aortic calcification (AAC) in US adults aged ≥40 years. Methods: Data was obtained from the 2013-2014 National Health and Nutrition Examination Survey (NHANES). Participants who less than 40 years old, missing the data of DII and AAC were excluded. DII was calculated based on a 24-h dietary recall interview for each participant. AAC score was quantified by assessing lateral spine images and severe AAC was defined as AAC score >6. Weighted multivariable regression analysis and subgroup analysis were preformed to estimate the independent relationship between DII with AAC score and severe AAC. Results: A total of 2897 participants were included with the mean DII of -0.17 ± 2.80 and the mean AAC score of 1.462 ± 3.290. The prevalence of severe AAC was 7.68% overall and participants in higher DII quartile trended to have higher rates of severe AAC (Quartile 1: 5.03%, Quartile 2: 7.44%, Quartile 3: 8.38%, Quartile 4: 10.46%, P=0.0016). A positive association between DII and AAC score was observed (β=0.055, 95%CI: 0.010, 0.101, P=0.01649) and higher DII was associated with an increased risk of severe AAC (OR=1.067, 95% CI: 1.004, 1.134, P=0.03746). Subgroup analysis indicated that this positive association between DII and AAC was similar in population with different gender, age, BMI, hypertension and diabetes status and could be appropriate for different population settings. Conclusion: Higher pro-inflammatory diet was associated with higher AAC score and increased risk of severe AAC. Anti-inflammatory dietary management maybe beneficial to reduce the risk of AAC.